A Rare Case of Absence of the Lateral Cutaneous Nerve of Forearm: Case Report - da Silveira, Helson Freitas; de Lucena, Jalles Dantas; Sobrinho, Osvaldo Pereira da Costa; Pessoa, Roberta Silva; Cerqueira, Gilberto Santos; Oliveira, André de Sá Braga; Ribeiro, Howard Lopes, Júnior (Journal of Morphological Sciences, 2019)
Introduction Variations in the formation and in the branching pattern of the brachial plexus are common. Numerous anastomotic variations between the musculocutaneous nerve (MCN) and the median nerve (MN) have been reported and could be implicated in a wide range of sensory and motor dysfunctions.Objective To report an uncommon case of an anastomotic variation between the MN and the MCN with a rare absence of the lateral cutaneous nerve of forearm (LCNF).Material and Methods A dissection of a male cadaver was performed at the Morphology Department of the Universidade Federal do Ceará, Fortaleza, state of Ceará, Brazil. The brachial plexus was exposed.Results It was observed that the MCN, after its origin in the lateral fasciculus of the brachial plexus, anastomoses with the MN in the middle third of the arm. It diverges from the most prevalent anatomical pattern, in which the MCN continues to pass distally beneath the brachii biceps, originating the LCNF. In this case, the MCN does not emit its main terminal branch, the LCNF, which innervates the lateral portion of the skin of the forearm. In the present case, the innervation of the lateral portion of the skin of the forearm is provided by radial nerve branches. The reported case has practical implications, since the absence of the LCNF could cause hypoesthesia in the skin of the forearm.Conclusion Thus, the knowledge of the formation and of the branching pattern of the brachial plexus is clinically important for the correct clinical interpretation of the sensory and motor disorders of the upper limbs caused by peripheral nerve injuries, as well as for planning surgical procedures to correct upper limb traumas.
Keywords: upper limb; median nerve; musculocutaneous nerve; lateral cutaneous nerve of forearm; brachial plexus